A pyroptosis-related gene signature for prognosis and immune microenvironment of pancreatic cancer - Tao, Sifan; Tian, Li; Wang, Xiaoyan; Shou, Yajun (Frontiers in Genetics, 2022)
Pancreatic cancer is one of the most lethal tumors owing to its unspecific symptoms during the early stage and multiple treatment resistances. Pyroptosis, a newly discovered gasdermin-mediated cell death, facilitates anti- or pro-tumor effects in a variety of cancers, whereas the impact of pyroptosis in pancreatic cancer remains unclear. Therefore, we downloaded RNA expression and clinic data from the TCGA-PAAD cohort and were surprised to find that most pyroptosis-related genes (PRGs) are not only overexpressed in tumor tissue but also strongly associated with overall survival. For their remarkable prognostic value, cox regression analysis and lasso regression were used to establish a five-gene signature. All patients were divided into low- and high-risk groups based on the media value of the risk score, and we discovered that low-risk patients had better outcomes in both the testing and validation cohorts using time ROC, nomograms, survival, and decision analysis. More importantly, a higher somatic mutation burden and less immune cell infiltration were found in the high-risk group. Following that, we predicted tumor response to chemotherapy and immunotherapy in both low- and high-risk groups, which suggests patients with low risk were more likely to respond to both immunotherapy and chemotherapy. To summarize, our study established an effective model that can help clinicians better predict patients’ drug responses and outcomes, and we also presented basic evidence for future pyroptosis related studies in pancreatic cancer.